ALGORITMA PENGATURAN KINEMATIKA ROBOT REDUNDANT UNTUK MENGHINDARI TERJADINYA TUMBUKAN BERDASARKAN SKEMA PRIORITAS TUGAS - SANTI ASTAWA, GEDE; GANDHIADI, G.K. (Jurnal Matematika; Vol. 1, No. 1 April 2007DO - 10.24843/JMAT.2007.v01.i01.p02)
A redundant manipulator has more degree of freedom than minimal needed to do its job. In this condition the manipulator can easily do the job, and can say become not optimal. To make the manipulator more optimal, we try to add some obstacles that must be avoided by the manipulator. in calculation process we use inverse kinematics method in task priority scheme. From the simulation result, it is looked that by adding some jobs do not annoy the main job of manipulator, and those prove that the priority of the job can help manipulator do that job more optimal.
Keywords: Task Priority, Kinematics, obstacle avoidance